Education and Development: Efforts to Measure Human Well-Being - Fargana Musayeva , Adalat Muradov, Yadulla Hasanli, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is evident from research on economic and social progress that economic growth does not always lead to social progress but, in some cases, leads to increased socio-political tension, social inequality and poverty. Even having increased production of aggregate product on background, the state of the population is deteriorating and economic growth does not provide for a fair distribution of income. A new approach to the concept of economic development began in the global economy in the late XX century. According to these approaches, economic growth cannot be considered as the main purpose and the indicator of development. In addition to economic growth, there are a number of indicators and their mutual relationship promote human development and well-being. This article examines the correlation between indicators characterizing the welfare of the population and economic growth, comparing the position of Azerbaijan in the accounts of international economic organizations on the relevant indicators. The authors did a comparative analysis with other countries, the impact of human development on people's incomes and the role of education in the wellbeing of the population.